2015
DOI: 10.1371/journal.pntd.0003877
|View full text |Cite
|
Sign up to set email alerts
|

Soil-Transmitted Helminths in Southwestern China: A Cross-Sectional Study of Links to Cognitive Ability, Nutrition, and School Performance among Children

Abstract: BackgroundEmpirical evidence suggests that the prevalence of soil-transmitted helminth (STH) infections in remote and poor rural areas is still high among children, the most vulnerable to infection. There is concern that STH infections may detrimentally affect children’s healthy development, including their cognitive ability, nutritional status, and school performance. Medical studies have not yet identified the exact nature of the impact STH infections have on children. The objective of this study is to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 23 publications
6
55
2
4
Order By: Relevance
“…Primary and middle schools are free in China. However, whereas most developed countries, and many developing countries, do not charge tuition for high school, China charges a minimum of $160 (in US dollars) per year, which is 27 percent of rural per capita income (Liu et al 2009). Indeed, academic high school tuition rates in China are among the highest in the world (Liu et al 2009).…”
Section: Lagging Human Capital Development For Rural Residentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary and middle schools are free in China. However, whereas most developed countries, and many developing countries, do not charge tuition for high school, China charges a minimum of $160 (in US dollars) per year, which is 27 percent of rural per capita income (Liu et al 2009). Indeed, academic high school tuition rates in China are among the highest in the world (Liu et al 2009).…”
Section: Lagging Human Capital Development For Rural Residentsmentioning
confidence: 99%
“…However, whereas most developed countries, and many developing countries, do not charge tuition for high school, China charges a minimum of $160 (in US dollars) per year, which is 27 percent of rural per capita income (Liu et al 2009). Indeed, academic high school tuition rates in China are among the highest in the world (Liu et al 2009). College tuition fees also are burdensome for students from poor rural areas, and students from those areas often do not qualify for need-based financial aid (Li, Meng, Shi, and Wu 2013;Loyalka et al 2013).…”
Section: Lagging Human Capital Development For Rural Residentsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Observational studies have found that chronic infection with STHs among school-aged children is associated with malnutrition and impaired growth, 4-6 cognitive impairment, 7,8 and lower school attendance. 9 These associations suggest that, in theory, reducing STH infection in children has the potential to improve nutrition and growth (i.e., hemoglobin levels, weight, height), cognitive abilities (i.e., working memory, processing speed), and school performance (i.e., school attendance, standardized test scores).…”
Section: Introductionmentioning
confidence: 99%
“…Серед них 42 % були інфіковані тим чи іншим видом круглих черв'яків (аскарида, волосоголов, кривоголовка дванадцятипала, некатор). Встановлено, що паразитар-на інфекція у дитини була асоційована із гіршими когні-тивними здатностями, нижчим нутритивним статусом, поганою шкільною успішністю [6]. Підтвердження не-гативного впливу паразитозу на розвиток дитини отри-мали і дослідники з Кенії, які вивчали поширеність та дію гельмінтів на зростаючий організм дитини протягом перших трьох років життя.…”
Section: вступunclassified